2001 Grolier multimedia encyclopedia (Danbury, Conn. Grolier Interactive, 2000)
The 2001 Grolier Multimedia Encyclopedia contains more than 60,000 well-researched articles as well as illustrations, panoramic images, video and sound. These are divided into 5 sections: articles, media, atlas, timelines, and a research starters section, that contains topics for school reports and research.
Includes: Nature : virtual serengeti.
Title from disc label.
System requirements for Windows: Pentium/100 or higher; Windows 2000, 98, 95 or NT Workstation 4.0 operating system; 16 MB memory; 32 MB recommended; 20 MB free hard-disk space minimal; 150 MB optimal; 16-bit stereo Sound Blaster card and speakers; "Double-speed' CD-ROM drive (300 KB/sec. or higher transfer rate); 256-colors, 640x480 resolution; thousands of colors, 800x600 recommended; Apple QuickTime 4.0(4.1.2 supplied with product); Direct X version 3.0 or later recommended by Apple for QT4; Microsoft mouse or compatible pointing device; printer (optional).
System requirements for Macintosh PowerMac 6100/66 or higher; Mac OS operating System 7.5.5 or higher; 8 MB of available RAM (in addition to that used by system); Apple QuickTime 4.0(4.1.2 supplied with product); "Double-speed' CD-ROM drive (300 KB/sec. or higher transfer rate); 256-colors, 640x480 resolution; thousands of colors, 800x600 recommended; (optional) modem; access to the World Wide Web using an Internet service provider.
Keywords: Electronic encyclopedias; Encyclopedias and dictionaries -- Databases; Electronic encyclopedias -- Interactive multimedia